Staff Training and Organizational Goals Attainment: A Study of Airtel Nigeria Networks - Iyewa, Victoria Irete; Gberevbie, Daniel Eseme (Covenant University Journal of Politics and International Affairs, 2017)
In today’s world, organizations including Airtel Nigeria Networks have come to realise that for them to be able to maintain a competitive edge over competitors, it is important to invest considerable amount of time and resources into the training of their workforce. Training which has to do with the acquisition of relevant skills or equipping employees with the needed knowledge to carry out specific duties or functions is quite vital for goals attainment. This is because training has the specific outcomes of improving the staff capability and capacity for performance. Without the training of its staff, an organisation is likely to find it difficult to have in its employment, the needed competent staff to attain its goals. In this regard, the study empirically examined how the training of staff facilitates attainment of goals of Airtel Nigeria Networks. With the utilisation of primary data obtained from respondents through the use of questionnaire, the study observed a significant relationship between staff training and organisational goals attainment of Airtel Nigeria Networks. It therefore, recommends that staff training in organisations should be sustained and enshrined as part of the organisation’s culture in order to achieve its goals of enhanced productivity at all times.